Contribution to the Hydrogeological Characterization of the Gardunha Mountain - Portugal. (2016) - Carvalho, Paulo; Pais, Luís; Gomes, Luís; Pinto, Luís; Lahuta, Hynek
Abstract: The present paper describes the hydrochemical evolution of mineral groundwater in the northeast area of Gardunha mountain (centre region of Portugal) which is formed by low permeability igneous rocks. For this study were considered 50 water samples and analyzed the values of major ions. The methodology used consisted in the use of Piper diagrams that had allowed to identify the water chemistry and in the application of statistical techniques of multivariate analysis, including factor analysis. The results guided to sodium-bicarbonate water type, with very low mineralization, designated by fresh water in relation to total solids and soft in relation to hardness. When using the factor analysis, 4 factors were considered, which explain and identify the origin of the presence of ions and their geochemical processes.